2000
DOI: 10.1210/endo.141.1.7236
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Expression of Prostaglandin H2Synthase in Late Pregnancy and during Parturition in Prostaglandin F Receptor-Deficient Mice1

Abstract: PG production in uterine tissues is important for many physiological processes in late pregnancy, including parturition. We examined the expression of the PGH2 synthases, cyclooxygenase-1 (COX-1) and COX-2, in uterine tissues during late pregnancy, using PGF receptor-deficient (FP-/-) mice. Female FP-/- mice are unable to deliver normal fetuses at term, as they do not undergo luteolysis necessary for parturition. In wild-type mice, COX-1 messenger RNA (mRNA) was expressed in the endometrial epithelium, myometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Accordingly, PG receptors in the myometrium are regulated to enhance the contractile response and relax the lower uterine segment during parturition (31)(32)(33)(34). Alternatively, Tsuboi et al suggest that COX-1-derived PGs are responsible for luteolysis, whereas COX-2-derived PGs are produced at a later stage of labor and are associated with the final steps of parturition (29). In our studies, COX-2 expression was highest in decidual cells.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…Accordingly, PG receptors in the myometrium are regulated to enhance the contractile response and relax the lower uterine segment during parturition (31)(32)(33)(34). Alternatively, Tsuboi et al suggest that COX-1-derived PGs are responsible for luteolysis, whereas COX-2-derived PGs are produced at a later stage of labor and are associated with the final steps of parturition (29). In our studies, COX-2 expression was highest in decidual cells.…”
Section: Discussionmentioning
confidence: 40%
“…COX-1 is expressed in the uterine luminal epithelium around the fetus, with extension throughout the interimplantation sites. Although COX-1 expression has been described in the mouse decidua (9), we and others (29) have shown that COX-1 is predominantly expressed in the uterine epithelium. Polarized cells secrete PGs apically or basolaterally (30).…”
Section: Discussionmentioning
confidence: 53%
“…These observations indicate that AP-1 plays a key role in the inflammation-mediated induction of labor9. COX2 is a highly inducible gene that is expressed at low to undetectable levels in the uterus throughout most of pregnancy, and it is highly up-regulated by proinflammatory cytokines and E 2 at term1011. COX2 catalyzes the production of prostaglandins in the amnion12 and plays a crucial physiological role in the initiation of labor by functioning as a potent activator of uterine contractility13.…”
mentioning
confidence: 99%
“…1C,D). It was previously thought that Cox-1-derived prostaglandins directly stimulate myometrial contractility or that PGF2α acts on the corpus luteum, leading to subsequent luteolysis, progesterone fall, and uterine activation for labor 61 . The compensatory mechanisms enabling normal uterine contractions in Cox-1 KO mice are not yet fully understood, but support an impaired cervical remodeling hypothesis that was tested in the current study.…”
Section: Discussionmentioning
confidence: 99%